2006
DOI: 10.1007/s10815-006-9039-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Preimplantation Embryo Development (Ped) Gene on Embryonic Platelet-Activating Factor (PAF) Levels

Abstract: The Ped gene plays a role in PAF production and release in preimplantation stage embryos. The use of two mouse identical strains, except for the Ped gene, show that its presence is associated with an increase in developmental potential. Embryos where the Ped gene was absent produced significantly higher levels of PAF, which may aid in their survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…There is precedence for the presence vs. the absence of the genes encoding the Ped gene phenotype affecting the expression of another molecule. Absence of Qa-2 expression has been shown to result in higher expression of platelet activating factor (PAF), a protein known to be beneficial to reproductive success [34]. From the findings with PAF and the results reported in the present paper we can conclude that the presence or absence of the Qa-2 encoding genes can affect both protein and miRNA expression levels in preimplantation embryos.…”
Section: Discussionsupporting
confidence: 66%
“…There is precedence for the presence vs. the absence of the genes encoding the Ped gene phenotype affecting the expression of another molecule. Absence of Qa-2 expression has been shown to result in higher expression of platelet activating factor (PAF), a protein known to be beneficial to reproductive success [34]. From the findings with PAF and the results reported in the present paper we can conclude that the presence or absence of the Qa-2 encoding genes can affect both protein and miRNA expression levels in preimplantation embryos.…”
Section: Discussionsupporting
confidence: 66%
“…These genomic regions harbor strong candidate genes implicated in cellular functions related to placental development and fetal growth, such as PAFAH2, CLIC4, and WNT4 (BTA2, 126.70–128.26 Mb), and CHAC1, CHST14 , and DLL4 (BTA10, 33.62–35.56 Mb). The PAFAH2 gene has been implicated in various stages of reproduction, including implantation, fetal development, and parturition 26 . The PAFAH2 gene stimulates the formation of IP3 and DAG and increases intracellular calcium 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The uniformly poor development of B6 embryos (whether cultured individually or communally) and the benefits of exogenous tropic ligands, indicate that embryos of this strain may have a profound deficiency of production of autocrine trophic ligands in vitro. It has been shown that the release of the autocrine embryotrophic ligand (Paf) is under genetic control [ 22 ] and this might also apply to other autocrine trophic ligands. The well characterised high level of sensitivity of B6 strain embryos to culture in vitro [ 19 ] has been shown to be associated with the loss of P53 regulation by trophic ligands in vitro [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inbred C57BL/6 J (B6) strain is particularly sensitive to culture in simple defined media, compared to the robust growth response of a hybrid strain [ 19 ]. Of interest, the release of putative trophic ligands may also be associated to the genetic background in mice [ 20 - 22 ].…”
Section: Introductionmentioning
confidence: 99%